1α,25(oh)2 d3 -glycosides and synthetic 1α,25(oh)2 d3 actions in cell cycle and myogenesis of c2c12 skeletal muscle cells - Irazoqui, Ana Paula (2017)
Solanum glaucophyllum leaf´s extracts (SGE) enriched with 1a,25(OH)2VitaminD3-glucosides are available for the organism due to the presence of endogenous glycosidases. We have shown that SGE alike 1a,25(OH)2D3 (1,25D) induces myoblast differentiation. In this work, we investigate Akt role in myoblast fusion to form myotubes during differentiation. The fusion index was determine staining C2C2 cells with MitoTracker Red prior fixation, cells were then stained with DAPI, and examined by fluorescence microscopy. We found that the ability of vitamin D compounds, 1,25D or SGE, to induce myotube formation was impaired in presence of Akt inhibitor LY294002. Since Akt inhibitor suppresses myotube formation, we investigate whether Akt participates in the late differentiation marker MHC2b expression founding that its mRNA expression was induced by 1,25D and SGE in an Akt dependent manner. The commitment of myogenic cells in skeletal muscle differentiation requires earlier irreversible interruption of the cell cycle. To evaluate the effect of SGE on the distribution of C2C12 cells into different phases of the cell cycle, we performed flow cytometry assays. The studies showed that SGE, similarly to 1,25D, prompts a peak of S-phase followed by an arrest in the G0/G1-phase, events which were dependent on the MAP kinases ERK1/2, p38 and JNK. We also investigated whether 1,25D or SGE regulate the immediate early gene c-myc in C2C12 cells undergoing proliferation. We found that 1,25D nor SGE induce c-myc mRNA expression, but both compounds increase c-myc protein levels, perhaps due to a decrease in protein degradation rate. Significant differences of the data between control and treated conditions were analyzed by one way-ANOVA followed by Bonferroni test (p<0.05) or t-test (*p<0.05, **p<0.01). Taken together, these results suggest that SGE, as 1,25D, promotes myotube formation through Akt activation and regulates c-myc protein and the cell cycle through ERK1/2, p38 and JNK.